PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE (STUDI PEMBELIAN OLEH GENERASI Z) - Listia, Rosa Vavita; Ernestivita, Gesty; Suhardi (Universitas Nusantara PGRI Kediri, 2022)
Marketplace Shopee as a business player must know what consumers need and be able to identify consumer behavior in making a purchase decision so that they can win the competition. Generation Z is known as the net gene. They are always in cyberspace and can do everything using technology. This study uses quantitative causality. The population is exclusively Gen Z who shop on the Shopee marketplace. Consists of 40 respondents with SPSS version 23. The results show that: 1) Product quality and promotion partially have a significant impact on purchasing decisions in the Shopee marketplace; 2) Price partially does not have a significant impact on purchasing decisions in the Shopee marketplace; 3) Product quality, price and promotion simultaneously have a significant impact on purchasing decisions in the Shopee marketplace.